Informação, voluntariado e redes digitais - Ayres, Bruno Ricardo Costa (2003)
This dissertation aims to understand the role, possibilities and limits of information in promoting and supporting volunteer actions. Today, there is a strong mobilization in society for the engagement in volunteer actions, although there are not enough volunteer opportunities for everyone. It is postulated here that the dissemination of information about volunteers and their actions can contribute to broaden the ways for volunteering. The focus of this research is the information that flows through digital networks, such as the Internet. Arguments are presented here about the various ways in which information can be disseminated to enlarge the perception of society about the diversity of meanings and possibilities of volunteer actions, and that contribute to both reach an individual s subjectivity and empower him/her minimally for volunteer action. Also, it is established that there are some conditions for the information to act as a mobilizer and generator of interactions and synergy among volunteers. The research field is the Portal do Voluntário, a website focused on volunteerism. The Portal s strategy for the dissemination of information about volunteerism and the interactions among the volunteers connected through it are thoroughly explored. Not ignoring the severe digital divide in Brazil, the study of the interactions among volunteers connected through a network such as the Internet, paves the way to overcoming the usual barriers for volunteer participation.